"IN SANJHI LOKKALA: RANGO SE CHARMA" (WITH SPECIAL REFERENCE TO LOK SANSKRITI MANCH INDORE): ‘‘सांझी लोककला में: रंगो से आकर्षण’’ (लोकसंस्कृति मंच इंदौर के विशेष संदर्भ में) - Chauhan, Manorama; Soni, Sheetal (International Journal of Research -GRANTHAALAYAH, 2014)
Folk art is a compound form of two words (folk $ art). The word "folk" is used to refer to the whole community who work together and "art" refers to the action of shaping the imagination. That is, the method of shaping their imagination by the particular population is called folk art. Malvanchal is the heartland of Madhya Pradesh and it has a special Indore city. The people here are still religious and cherish their culture. Apart from the natural, cultural, literary and social environment, folk culture, folk literature, folk music, and folk art are also rich here. It has a folk art called "Sanja". In this Shraddha Paksha, the virgin girls perform this festival every year from the full moon of Bhadwa month to the new moon of Ashwin month to get a good brides through Sanja Pujan and fasting. Just as Parvati ji had received Lord Shankar through Sanja Vrata. लोककला दो शब्दों का मिश्रित रूप है (लोक$कला) लोककला। ‘‘लोक’’ शब्द का प्रयोग उस सम्पूर्ण जनसमुदाय के लिए किया जाता है जो साथ मिलकर कार्य को करते है तथा ‘‘कला’’ कल्पनाओं को आकार देने कि क्रिया को कहते है। अर्थात विशेष जनसमुदाय द्वारा उनकी कल्पना को आकार देने की पद्धती को लोककला कहा जाता है। मालवांचल मध्यप्रदेश का हृदय स्थल है तथा इसमें विशेष इन्दौर शहर है यहां की जनता आज भी धर्मप्रेमी तथा अपनी संसकृति संजोए हुए है। यहाँ के अनुकूल प्राकृतिक, सांस्कृतिक, साहित्यिक एवं सामाजिक वातावरण के साथ ही लोक संस्कृति लोक साहित्य, लोक संगीत, एवं लोककला भी समृद्ध है। इसमें एक लोककला है ‘‘संजा’’। इस लोककला पर्व को कुँवारी लड़कीयाँ श्राद्ध पक्ष में हर वर्ष भादवा माह की पूर्णिमा से अश्विन माह की अमावस्या तक अच्छा वर पाने के लिए संजा पूजन एवं व्रत-उपवास के माध्यम से करती है। जिस प्रकार पार्वती जी ने भगवान शंकर को संजा वृत के द्वारा प्राप्त किया था।